Prevalence and influencing factors of anemia among pregnant women across first, second and third trimesters of pregnancy in monitoring areas, from 2016 to 2020: a population-based multi-center cohort study - Yuting Qiao; Jiangli Di; Lina Yin; Aiqun Huang; Wei Zhao; Huanqing Hu; Sidi Chen (BMC, 2024)
Abstract Objective To assess the prevalence of anemia among pregnant women across their entire pregnancy and the factors affecting it in the monitoring areas. Methods A total of 108,351 pregnant women who received antenatal health care and delivered from January 1, 2016 to December 31, 2020 in 15 monitoring counties of 8 provinces in the Maternal and Newborn Health Monitoring Program (MNHMP) of National Center for Women and Children's Health (NCWCH) were selected as the study subjects. The anemia status among the subjects across their first, second and third trimester of pregnancy and the influencing factors were analyzed. Results From 2016 to 2020, the prevalence of anemia at any stage during pregnancy in the monitoring areas was 43.59%. The prevalence of anemia among pregnant women across all three trimesters was 3.95%, and the prevalence of mild and moderate-to-severe anemia was 1.04% and 2.90%, respectively. Protective factors were living in the northern area (OR = 0.395) and being a member of an ethnic minority (OR = 0.632). The risk factors were residing in rural areas (OR = 1.207), with no more than junior high school education (OR = 1.203), having ≥ 3 gravidities (OR = 1.195) and multiple fetuses (OR = 1.478). Conclusions Although the prevalence of anemia among pregnant women across all trimesters in the monitoring area was low, the severity of anemia was high. Since the prevalence of anemia among pregnant women across their entire pregnancy in the monitoring area is affected by many different factors, more attention should be paid to pregnant women living in rural areas, with low literacy, ≥ 3 gravidities and multiple fetuses for early intervention.